The Fractured Republic : Renewing America's Social Contract in the Age of Individualism - Levin, Yuval (Basic Books, A Member of the Perseus Books Group, 2016)
"How America can overcome nostalgia, revive civil society, and thrive in the twenty-first century"--Publisher.